The Practical Used of Essay Writing Material based PjBL through Padlet in Higher Education - Ahmad, Arimuliani; Mukhaiyar; Atmazaki; Johari, Afrizal (International Journal of Language Pedagogy, 2023)
Mastering essay writing skill is crucial for students who majoring in English Language Department to enhance their language proficiency development, critical thinking, effective communication, and prepares them for academic and professional demands. Meanwhile, many problems still occur in mastering this skill. Hence, the requirement for innovation in teaching essay writing, especially for Essay Writing course is needed. This research used survey method to investigate the practical used of of Essay Writing material-based Project-based Learning through Padlet for teaching Essay Writing course. There were 50 students and 3 lecturers who were involved in the initial investigation of this study. Then, 3 students for limited trials, and 63 students involved in wide trials. The practicality result shows that the teaching material are categorized as Very Practical (85.8%) from teachers’ perspective and Very Practical (84.1%) from students’ perspective. Addressing that explanation about this research finding, it can be concluded that this Instructional Material based PjBL through Padlet is effective to be applied in higher education with independent students to enhance their creative, innovative and critical thinking in expressing ideas about authentic problem in their environment and world- wide environment.